The minimum wage affects them all: Evidence on employment spillovers in the roofing sector - Bodo Aretz; Melanie Arntz; Terry Gregory (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2012)
This paper contributes to the sparse literature on employment spillovers on minimum wages by exploiting the minimum wage introduction and subsequent increases in the German roofing sector that gave rise to an internationally unprecedented hard bite of a minimum wage. We look at the chances of remaining employed in the roofing sector for workers with and without a binding minimum wage and use the plumbing sector that is not subject to a minimum wage as a suitable benchmark sector. By estimating the counterfactual wage that plumbers would receive in the roofing sector given their characteristics, we are able to identify employment effects along the entire wage distribution. The results indicate that the chances for roofers to remain employed in the sector in eastern Germany deteriorated along the entire wage distribution. Such employment spillovers to workers without a binding minimum wage may result from scale effects and/or capital-labour substitution.
urn:nbn:de:bsz:180-madoc-325663
Keywords: J38; J21; J23; 330; minimum wage; Germany; capital-labour substitution; labour-labour substitution; scale effect